Analisis Kadar Air, Kadar Protein dan Karakteristik Organoleptik Kerupuk Stik dengan Penambahan Konsentrasi Ikan Layang yang Berbeda - Febriana Muchtar; Hastian Hastian; Ruksanan Ruksanan (Ma'soem University, 2023)
This study was performed to examine the effect of different concentrations of mackerel scads fish on water content, protein content and organoleptic properties of mackerel scads stick crackers. This research was conducted using an experimental method with a non-factorial Completely Randomized Design (CRD).The treatment applied was in different concentrations of mackerel scads fish consisted of 3 levels of treatment, namely, 20% (L1), 30% (L2) and 40% (L3). Each treatment was replicated three times. Data of this study were analyzed by using one- way Anova and was followed by a Duncan test with ? = 5% if there was a significant difference between treatments. Water content was tested using oven method, while the protein content was measured using Kjedhal method and organoleptic properties were tested in hedonic test (favorability level). The results showed that fish concentrations affected the water content, protein content and organoleptic properties of mackerel scads fish stick crackers, including the color, aroma and taste. However, the texture of fish stick crackers was not affected. The treatment with 30% (L2) of mackerel scads fish meat showed the most of optimal outcomes with, 4.24% water content, 25.03% protein content, and organoleptic properties of color 4.37 (like), aroma 4.49 (like), texture 4.60 (strongly like) and 4.49 (like).